Simulated memory error and blame attribution in cases of child sexual abuse - Hong, Maxwell R. (Psychology, crime & law, 2021)
The present study utilized simulated memory error and blame attributions to investigate the effects of variations in rehearsal on memory. Specifically, 222 undergraduates read a story about child sexual abuse (CSA) while role-playing as the main character. After reading the story, participants were prompted to blame different characters for the abuse (perpetrator, mother, self, or no one) and rehearse the story (to write out the story while incorporating their blame attributions or to write out the story without adding blame attributions), or not rehearse (to not write out the story). Due to prior research on simulated memory error and memory for CSA, we collected data on participant depression, posttraumatic stress disorder, dissociative tendencies, emotion regulation strategies, and attachment orientation. After a 2-week delay, participants were asked to write out the entire story exactly as they had read it. We found that rehearsal resulted in fewer omission errors, and blame attribution predicted more omission errors. Cognitive reappraisal was associated with more commission errors and fewer omission errors. Males and participants with higher psychopathology scores also made more omission errors. There was also an interaction between different attachment systems when predicting commission errors.